2016
DOI: 10.1161/circheartfailure.116.003423
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor-1α Mediates Increased Sympathoexcitation via Glutamatergic N-Methyl- d -Aspartate Receptors in the Paraventricular Nucleus of Rats With Chronic Heart Failure

Abstract: Background Increased sympathetic outflow is a major contributor to the progression of chronic heart failure (CHF). Potentiation of glutamatergic tone has been causally related to the sympathoexcitation in CHF. Specifically, an increase in the N-methyl-D-aspartate-type1 receptor (NMDA-NR1) expression within the paraventricular nucleus (PVN) is critically linked to the increased sympathoexcitation during CHF. However, the molecular mechanism(s) for the up-regulation of NMDA-NR1 remains unexplored. We hypothesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 63 publications
(72 reference statements)
2
17
0
1
Order By: Relevance
“…We have shown that basal ARNA was higher in HF than Sham consistent with our previous report [26] as well as basal RSNA [29,32,33]. Intrapelvic injection of GLP-1 increased ARNA and this response was 1.5-fold greater in HF compared to Sham.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We have shown that basal ARNA was higher in HF than Sham consistent with our previous report [26] as well as basal RSNA [29,32,33]. Intrapelvic injection of GLP-1 increased ARNA and this response was 1.5-fold greater in HF compared to Sham.…”
Section: Discussionsupporting
confidence: 91%
“…This anesthetic is specifically chosen to minimize the effects of anesthesia on central pathways involved in autonomic regulation of the cardiovascular system. Under this anesthesia a lot of the autonomic reflex functions are studied and are operational [24,26,29,[31][32][33] and therefore being used in current study examining effects of GLP-1 on neural circuitry of renal nerve activity involved in central nervous system. Body temperature was controlled at 36-38 °C by a stage heater.…”
Section: Intrapelvic Injection Of Glp-1 With Direct Recording Of Affementioning
confidence: 99%
“…34 In the vein of thyroid hormone, NMDA-R activation has been linked to some kind of circulatory diseases, such as heart failure, cardiac arrhythmias and hypertension. [6][7][8][9][10] Therefore, it is rational to assume that the NMDA-R could be a prospective intervention target for the T4-induced cardiovascular changes and we believe that this is the first study to examine this hypothesis.…”
Section: Discussionmentioning
confidence: 95%
“…50 Additionally, it has been reported that memantine could prevent the reduction in the rat LV cardiomyocyte nuclear size induced by cold stress, which has been suggested to either initiate or increase the rodent cardiovascular dysfunction, 51,52 concluding that memantine might be a promising cardioprotective medication. 51 Actually, NMDA-R has been shown to play a key role in the induction of several heart failure/decreased cardiac contractility related pathways, such as the sympathoexcitation, 6,7 oxidative stress, calcium overload, cardiomyocyte apoptosis, 1,53 myocardial fibrosis 8 and stimulation of myocyte mitochondrial matrix metalloproteinase. 11 Even though T4-induced cardiac remodeling has been referred to similar mechanisms, including the sympathetic nervous system, 54 oxidative stress, 19,20 cardiomyocyte apoptosis 21 and matrix metalloproteinase, 22 memantine could not inhibit any of the T4-induced cardiac pathological manifestations in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation